2007
DOI: 10.1016/j.otohns.2006.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal corticosteroid use is associated with lower rates of bacterial recovery in chronic rhinosinusitis

Abstract: The results suggest a possible role of INCS in the management of post-ESS disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 16 publications
3
22
0
1
Order By: Relevance
“…Bacteria identified in this study as well as the other CRS biofilm studies have generally found that 70% of the infections identified were secondary to Pseudomonas aeruginosa or Staphylococcus aureus, and they were often polymicrobial in nature. These results demonstrate that biofilms are present in most patients with CRS and that the bacteriology of these biofilms may not differ radically from the current paradigm for the bacteriology of CRS [23,24]. However, given our general understanding of the propensity of bacteria to form a biofilm, these findings are not completely unexpected.…”
Section: Evidence That Biofilms Exist In Chronic Rhinosinusitismentioning
confidence: 62%
“…Bacteria identified in this study as well as the other CRS biofilm studies have generally found that 70% of the infections identified were secondary to Pseudomonas aeruginosa or Staphylococcus aureus, and they were often polymicrobial in nature. These results demonstrate that biofilms are present in most patients with CRS and that the bacteriology of these biofilms may not differ radically from the current paradigm for the bacteriology of CRS [23,24]. However, given our general understanding of the propensity of bacteria to form a biofilm, these findings are not completely unexpected.…”
Section: Evidence That Biofilms Exist In Chronic Rhinosinusitismentioning
confidence: 62%
“…In numerous studies of the bacteriology of CRS done with conventional culture methods, Staphylococcus aureus has been implicated as one of the most common bacteria to colonize the paranasal sinuses in both asymptomatic postoperative and operative patients with CRS [35,36]. As such, this organism has been demonstrated to occur in the form of a biofilm in patients with CRS, as have coagulase-negative Staphylococcus (CNS), P. aeruginosa, and H. influenzae [37][38][39][40].…”
Section: Previous Evidencementioning
confidence: 99%
“…[24][25][26] However, the adverse effects of the immunosuppressive effect of GCs have also been a concern in the treatment of CRS. 12 Our results showed that INCS, which was used continuously for one month in CRS patients, did not change the bacterial culture rate, distribution of bacteria, or antibiotic sensitivity. This suggests that using INCS is relatively safe for CRS patients.…”
Section: Discussionmentioning
confidence: 53%
“…A previous study showed that topical intranasal corticosteroids could decrease the recovery rate of bacteria from the ethmoid sinuses in cases undergoing sinus surgery for chronic rhinosinusitis. 12 This means that INCS has an anti-inflammatory effect in such patients. From our results, the bacterial culture rate and drug sensitivity did not change after using INCS for one month in CRS patients with nasal polyposis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation